2007
DOI: 10.1007/s11606-006-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Physician–Patient Communication About Prescription Medication Nonadherence: A 50-state Study of America’s Seniors

Abstract: CONTEXT: Understanding and improving the quality of medication management is particularly important in the context of the Medicare prescription drug benefit that took effect last January 2006. OBJECTIVE:To determine the prevalence of physicianpatient dialogue about medication cost and medication adherence among elderly adults nationwide. DESIGN:Cross-sectional survey.PARTICIPANTS: National stratified random sample of community-dwelling Medicare beneficiaries aged 65 and older. MAIN OUTCOME MEASURES:Rates of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(150 citation statements)
references
References 26 publications
4
144
0
2
Order By: Relevance
“…That is, more than half of all people with COPD who have been referred to a pulmonary rehabilitation programme have at least one other chronic condition [30] and, therefore, medication burden in this group is likely to be high. Among elderly adults who have been prescribed multiple medications, nonadherence to pharmacotherapy regimens is problematic [31], which, in turn, increases the risk of hospitalisation and mortality [32]. Thus pulmonary rehabilitation offers the opportunity to review medication use and implement strategies to optimise adherence.…”
Section: Optimising Pharmacotherapymentioning
confidence: 99%
“…That is, more than half of all people with COPD who have been referred to a pulmonary rehabilitation programme have at least one other chronic condition [30] and, therefore, medication burden in this group is likely to be high. Among elderly adults who have been prescribed multiple medications, nonadherence to pharmacotherapy regimens is problematic [31], which, in turn, increases the risk of hospitalisation and mortality [32]. Thus pulmonary rehabilitation offers the opportunity to review medication use and implement strategies to optimise adherence.…”
Section: Optimising Pharmacotherapymentioning
confidence: 99%
“…[1][2][3][4] Those with limited literacy skills and English proficiency (LEP) are disproportionately at risk. [2][3][4][5][6][7][8][9] The manner in which physicians convey prescription instructions and pharmacy labeling practices has consequently been scrutinized as possible root causes of the confusion. [10][11][12][13][14] This body of research has now been summarized at great length in numerous seminal reports, all recognizing the urgent need to improve written medication instructions and prescription labeling, both to promote patient safety and to improve adherence.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Yet, in 1 study of Part D beneficiaries with diabetes, less than one-half of patients discussed drug costs with their physicians. 24 Another study found that 40% of physicians reported that, at least once in the previous 30 days, they had not discussed cost with their patients but wished they had.…”
Section: ■■ Discussionmentioning
confidence: 99%